Meningkatkan Kemampuan Membaca Permulaan melalui Kegitan Bermain Kartu Huruf Bergamabar pada Kelompok B TK Harapan Kelayu Kecamatan Selong Tahun Pelajaran 2020/2021 - Kurniati, Kurniati (MASALIQ, 2021)
The objectives of this classroom action research (CAR) are. knowing the improvement of early reading skills through picture card playing activities in group B. Early Childhood Education TK Harapan Kelayu, Selong District 2016/2017. In this class action research (CAR) was carried out in 2 cycles, from the results of the actions taken it was proven to be able to increase student learning mastery classically, namely in the first cycle by 60%, it could increase to 100% in cycle II. The results of this classroom action research show that learning by applying pictorial letter cards can improve the quality of learning and student learning mastery in language skills subjects with completeness reaching 100%.